Book Review. Time Travels in a Bilingual Lyrical Dialogue: Rodica Marian’s and Michaela Mudure’s Book of Poems/Poeme (Papers in Arts and Humanities, 2022)
Perhaps we may only come to understand the poems written in our mother tongue after their necessary linguistic defamiliarization, once they are rendered in another language. By this defamiliarizing (re/de)construction, doubled by translation, not only does the reader never get lost, but on the contrary, it is the translator's refreshing vision that deepens the poet's metaphorical meaning. The (memory of the) original poem becomes the new poem, and thus the reader is privileged by a kaleidoscopic view, forever in the (un/re)making, an ever more vivid image of the (same) rainbow light, unpredictably filtered through the other lenses. Poet Rodica Marian and translator Michaela Mudure are thus taking together an introspective trip in time, through the ages (and stages) of poetic conscience. The success of their lyrical dialogue/journey lies in their finding a poetic language of their own, beyond (conventional) linguistic frontiers. If we may regard Marian's verse as a Romanian version of confessional poetry, we must also rely on Mudure's choice of the poems here translated as on an astute, insightful, and scholarly confirmation.
Keywords: time; (self)transcendence Transylvania travel; (self)quest/portrait